O Xadrez Diplomático da América Latina Frente aos Conflitos Internacionais - Ceregatte Rosario, João Vitor (2025)
The article addresses the challenges faced by Latin America in the 21st century, highlighting the complexity of inter-regional conflicts and the influence of external actors, such as the United States. With a past full of political instability, social inequality, and violence, the region seeks integration and autonomy through institutions. However, internal divergences, the migration crisis, the rise of organized crime, and geopolitical tensions hinder the construction of a stable and prosperous future. Brazil's leadership and collaboration between regions are considered fundamental factors that overcome obstacles and drive sustainable growth.